Efecto del tiempo de envejecido en la estructura cristalina y las propiedades mecánicas del aluminio 6061 (2020)
In this project, an analysis of the effect of aging time on the crystalline structure and mechanical properties of aluminum alloy 6061 was carried out. Aging is one of the 3 stages which is part a set of more complex heat treatments known as age hardening. The sequence used in this work was: First, the temperature was raised to obtain a homogeneous phase on the sample at a temperature of 530 ºC for 2 hours, this step is called a solution treatment. In the second stage, referred as quenching the material in the solid solution state was rapidly cooled in water to room temperature and allowed to rest for 4 hours. In the third stage, the material was heated to a temperature of 175 ºC and kept at different aging times. This aging process, also called maturation, has been reported to improve the mechanical properties of 6061 aluminum and produce changes in its crystalline structure. The different maturation times evaluated were 15 min, 90 min, 8 am and 6 pm. Changes in tensile strength were evaluated under standard ASTM E8M. Likewise, the variation in the material hardness was evaluated for different maturation times, the performance of Vickers microindentation hardness tests under standard ASTM E384. In each test was evidenced the specimens got their maximum hardening at 18 hours of aging.